High-performance composite plastic for new energy battery shell and preparation method of high-performance composite plastic

By using the combination technology of montmorillonite and graphene composite thermal conductor in the shell materials of new energy batteries, combining toughener, dispersant and antioxidant to form high-performance composite plastics, the materials are solved in impact resistance, heat sealing and resistance. The shortcomings in combustion and low-temperature impact resistance have achieved higher performance improvements.

CN119431951APending Publication Date: 2025-02-14Guangdong Yuhao New Materials Technology Research Institute
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411571829.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing materials used in new energy battery shells have shortcomings in impact resistance, heat sealing performance, flame retardant performance and low-temperature impact resistance, and composite materials also have problems in electrolyte corrosion.

Method used

Montmorillonite is used to expand and intercalate in the graphene composite thermal conducting agent, and then peeling occurs. Toughening agent, dispersing agent and antioxidant are combined and deposited in the slab structure of the montmorillonite. KH560 coupling agent is hydrolyzed to form silanol. , bonding with polypropylene more closely to form high-performance composite plastic.

Benefits of technology

It has achieved significant improvements in impact resistance, thermal conductivity, flame retardant properties and impact resistance of high-performance composite plastics, solving the shortcomings of the materials in electrolyte corrosion and low-temperature impact resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431951A_ABST
    Figure CN119431951A_ABST
Patent Text Reader

Abstract

The invention discloses high-performance composite plastic for a new energy battery shell and a preparation method of the high-performance composite plastic, and belongs to the technical field of composite plastic. The high-performance composite plastic comprises the following components in parts by weight: 30-50 parts of polypropylene, 20-40 parts of polyethylene, 15-18 parts of montmorillonite, 1-3 parts of a coupling agent, 10-20 parts of graphene, 1-3 parts of a toughening agent, 3-5 parts of a dispersing agent and 1-5 parts of an antioxidant. According to the invention, montmorillonite is expanded and intercalated in the graphene composite heat-conducting agent, then stripping is carried out, the flexibilizer, the dispersant and the antioxidant are combined and deposited in the lamellar structure of montmorillonite, the KH560 coupling agent is hydrolyzed to form silanol, the silanol is combined with polypropylene more tightly, and the impact resistance is excellent, which is difficult to achieve by using the KH560 coupling agent alone. A three-dimensional heat-conducting skeleton network is easily formed in the heat-conducting plastic prepared by the invention; the preparation process is simple, and the stamping resistance and flame retardance are high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite plastics, and specifically refers to a high-performance composite plastic for a new energy battery casing and a preparation method thereof. Background Art

[0002] The automobile industry is developing rapidly, but energy issues are becoming increasingly urgent, and the environmental problems caused by automobiles are also attracting much attention. Developing the new energy automobile industry is an effective way to alleviate the energy crisis, reduce greenhouse gas emissions, and reduce environmental pollution. At present, new energy vehicles have become an important direction for the transformation of the automobile industry. New energy vehicles are different from traditional vehicles. They use batteries as power to drive the car. They are restricted by the weight of the power battery, the mileage of the power battery, and the high pressure of the automobile energy conservation and emission reduction policy. The lithium battery shell has high requirements for impact resistance, and the combination between the battery slot and the battery cover is heat-sealed, which requires the shell material to have good heat-sealing performance. At the same time, the shell material of the lithium battery needs to have excellent flame retardant properties and good mechanical properties, especially low-temperature impact resistance.

[0003] Polypropylene is a thermoplastic with light specific gravity, high surface hardness, high elasticity, good heat resistance, chemical stability and insulation, and is widely used in many fields of production and life. However, polypropylene is extremely flammable, with a limiting oxygen index of only 17.4-18.5, and serious droplets during combustion, which can easily spread flames and cause fires, making its application unsafe. At the same time, its quality is unstable and fluctuates too much, so it cannot be mass-produced, which limits the use of high-impact polypropylene materials in the manufacture of new energy battery shells.

[0004] Among the flame retardants currently used in flame-retardant polypropylene materials, halogen-free flame retardant zinc borate is favored because of its low smoke and environmental protection advantages. However, zinc borate is hydrophilic and oleophobic, and it is difficult to disperse evenly in the material when blended with polypropylene, which has a significant negative impact on the low-temperature impact resistance of polypropylene. The Chinese patent number is CN201110459943.7, which provides a composite plastic and a lithium-ion battery and battery pack made of it and an assembly method thereof. The composite reinforcing filler and composite thermal conductive filler in the patent have serious deficiencies in resisting electrolyte corrosion. The hydrofluoric acid in the electrolyte will react with the composite material, causing the battery shell to fail. The addition of external fibers will cause capillary conduction between the inside and outside of the battery, causing micro-leakage of the electrolyte, and trace amounts of water will enter the battery to produce chemical reactions. Summary of the invention

[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a high-performance composite plastic for new energy battery shells and a preparation method thereof. The present invention uses montmorillonite to expand and intercalate in a graphene composite thermal conductor, and then peels off. The toughening agent, dispersant and antioxidant are combined and deposited in the montmorillonite layer structure. The KH560 coupling agent is hydrolyzed to form silanol, which is more tightly combined with polypropylene and has excellent impact resistance, which is difficult to achieve using the KH560 coupling agent alone. The thermally conductive plastic prepared by the present invention is easy to form a three-dimensional thermally conductive skeleton network inside; the preparation process of the present invention is simple, and it has strong anti-punching ability and flame retardancy.

[0006] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: a high-performance composite plastic for new energy battery shell and a preparation method thereof, wherein the high-performance composite plastic comprises the following components in parts by weight: 10-80 parts of polypropylene, 10-50 parts of polyethylene, 10-30 parts of montmorillonite, 1-10 parts of coupling agent, 10-40 parts of graphene, 0.2-10 parts of toughening agent, 1-8 parts of dispersant, and 0.5-20 parts of antioxidant.

[0007] Preferably, the high-performance composite plastic comprises the following components in parts by weight: 20-60 parts of polypropylene, 15-40 parts of polyethylene, 15-20 parts of montmorillonite, 1-5 parts of coupling agent, 10-30 parts of graphene, 0.5-5 parts of toughening agent, 2-8 parts of dispersant, and 1-10 parts of antioxidant.

[0008] Preferably, the high-performance composite plastic comprises the following components in parts by weight: 30-50 parts of polypropylene, 20-40 parts of polyethylene, 15-18 parts of montmorillonite, 1-3 parts of coupling agent, 10-20 parts of graphene, 1-3 parts of toughening agent, 3-5 parts of dispersant, and 1-5 parts of antioxidant.

[0009] Preferably, the density of the polyethylene is 0.941-0.960 g / cm 3 .

[0010] Preferably, the coupling agent is KH560 coupling agent.

[0011] Preferably, the toughening agent is one or more of maleic anhydride and chlorinated polyethylene.

[0012] Preferably, the dispersant is one or more of calcium stearate, aluminate, titanate and paraffin.

[0013] Preferably, the average particle size of the dispersant is 200-400 μm.

[0014] Preferably, the antioxidant is one or more of antioxidant 1076, antioxidant 3114 and antioxidant 1010.

[0015] The present invention also provides a method for preparing a high-performance composite plastic for a new energy battery housing, the preparation method comprising the following steps:

[0016] (1) mixing polypropylene, polyethylene, graphene, montmorillonite, and a coupling agent to obtain a graphene composite thermal conductor;

[0017] (2) mixing the graphene composite thermal conductor with a toughening agent, a dispersant and an antioxidant to obtain a graphene composite thermal conductive plastic blend;

[0018] (3) The graphene composite thermal conductive plastic blend is extruded and granulated to obtain the high-performance composite plastic.

[0019] The beneficial effects achieved by the present invention using the above structure are as follows: (1) the present invention uses montmorillonite to expand and intercalate in the graphene composite thermal conductor, and then peeling occurs, the toughening agent, dispersant and antioxidant are combined and deposited in the montmorillonite layer structure, the KH560 coupling agent is hydrolyzed to form silanol, which is more tightly combined with polypropylene and has excellent impact resistance, which is difficult to achieve using the KH560 coupling agent alone; (2) the thermal conductive plastic prepared by the present invention easily forms a three-dimensional thermal conductive skeleton network inside; (3) the preparation process of the present invention is simple, and has strong anti-punching ability and flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Thermal conductivity of high performance composite plastics.

[0021] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0024] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials and test strains used in the following examples are purchased from commercial channels unless otherwise specified.

[0025] Example 1

[0026] A high-performance composite plastic for new energy battery housing and preparation method thereof

[0027] The high-performance composite plastic comprises the following components in parts by weight: 30 parts of polypropylene, 20 parts of polyethylene, 15 parts of montmorillonite, 1 part of coupling agent, 10 parts of graphene, 1 part of toughening agent, 3 parts of dispersant and 1 part of antioxidant.

[0028] Wherein, the density of the polyethylene is 0.941-0.960 g / cm 3 .

[0029] Wherein, the coupling agent is KH560 coupling agent.

[0030] Wherein, the toughening agent is maleic anhydride.

[0031] Wherein, the dispersant is paraffin.

[0032] Wherein, the average particle size of the dispersant is 200-400 μm.

[0033] Wherein, the antioxidant is antioxidant 1076.

[0034] The present invention also provides a method for preparing a high-performance composite plastic for a new energy battery housing, the preparation method comprising the following steps:

[0035] (1) mixing polypropylene, polyethylene, graphene, montmorillonite, and a coupling agent to obtain a graphene composite thermal conductor;

[0036] (2) mixing the graphene composite thermal conductor with a toughening agent, a dispersant and an antioxidant to obtain a graphene composite thermal conductive plastic blend;

[0037] (3) The graphene composite thermal conductive plastic blend is extruded and granulated to obtain the high-performance composite plastic.

[0038] Example 2

[0039] A high-performance composite plastic for new energy battery housing and preparation method thereof

[0040] The high-performance composite plastic comprises the following components in parts by weight: 40 parts of polypropylene, 30 parts of polyethylene, 17 parts of montmorillonite, 2 parts of coupling agent, 15 parts of graphene, 2 parts of toughening agent, 4 parts of dispersant and 3 parts of antioxidant.

[0041] Wherein, the density of the polyethylene is 0.941-0.960 g / cm 3 .

[0042] Wherein, the coupling agent is KH560 coupling agent.

[0043] Wherein, the toughening agent is maleic anhydride.

[0044] Wherein, the dispersant is paraffin.

[0045] Wherein, the average particle size of the dispersant is 200-400 μm.

[0046] Wherein, the antioxidant is antioxidant 1076.

[0047] Example 3

[0048] A high-performance composite plastic for new energy battery housing and preparation method thereof

[0049] The high-performance composite plastic comprises the following components in parts by weight: 50 parts of polypropylene, 40 parts of polyethylene, 18 parts of montmorillonite, 3 parts of coupling agent, 20 parts of graphene, 3 parts of toughening agent, 5 parts of dispersant and 5 parts of antioxidant.

[0050] Wherein, the density of the polyethylene is 0.941-0.960 g / cm 3 .

[0051] Wherein, the coupling agent is KH560 coupling agent.

[0052] Wherein, the toughening agent is maleic anhydride.

[0053] Wherein, the dispersant is paraffin.

[0054] Wherein, the average particle size of the dispersant is 200-400 μm.

[0055] Wherein, the antioxidant is antioxidant 1076.

[0056] Experimental Example 1

[0057] Thermal conductivity test of a high-performance composite plastic for new energy battery housing

[0058] The high thermal conductivity composite plastic material for lithium ion battery casing prepared in Example 1, Example 2 and Example 3 was used as the experimental material and marked as Example 1 group, Example 2 group and Example 3 group, with three replicates in each group. The thermal conductivity of each group was tested using the GB / T10294-2008 method and the average value was taken.

[0059] like Figure 1As shown, the high-performance composite plastics of Example 1, Example 2 and Example 3 all have good thermal conductivity, among which the thermal conductivity of Example 3 is the best.

[0060] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0061] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.

Claims

1. A high-performance composite plastic for new energy battery housing, characterized in that: The high-performance composite plastic comprises the following components in parts by weight: 10-80 parts of polypropylene, 10-50 parts of polyethylene, 10-30 parts of montmorillonite, 1-10 parts of coupling agent, 10-40 parts of graphene, 0.2-10 parts of toughening agent, 1-8 parts of dispersant and 0.5-20 parts of antioxidant.

2. The high-performance composite plastic for new energy battery housing according to claim 1, characterized in that: The high-performance composite plastic comprises the following components in parts by weight: 20-60 parts of polypropylene, 15-40 parts of polyethylene, 15-20 parts of montmorillonite, 1-5 parts of coupling agent, 10-30 parts of graphene, 0.5-5 parts of toughening agent, 2-8 parts of dispersant and 1-10 parts of antioxidant.

3. The high-performance composite plastic for new energy battery housing according to claim 2, characterized in that: The high-performance composite plastic comprises the following components in parts by weight: 30-50 parts of polypropylene, 20-40 parts of polyethylene, 15-18 parts of montmorillonite, 1-3 parts of coupling agent, 10-20 parts of graphene, 1-3 parts of toughening agent, 3-5 parts of dispersant and 1-5 parts of antioxidant.

4. The high-performance composite plastic for new energy battery housing according to claim 3, characterized in that: The density of the polyethylene is 0.941-0.960 g / cm 3 .

5. The high-performance composite plastic for new energy battery housing according to claim 4, characterized in that: The coupling agent is KH560 coupling agent.

6. The high-performance composite plastic for new energy battery housing according to claim 5, characterized in that: The toughening agent is one or more of maleic anhydride and chlorinated polyethylene.

7. The high-performance composite plastic for new energy battery housing according to claim 6, characterized in that: The dispersant is one or more of calcium stearate, aluminate, titanate and paraffin.

8. The high-performance composite plastic for new energy battery housing according to claim 7, characterized in that: The average particle size of the dispersant is 200-400 μm.

9. The high-performance composite plastic for new energy battery housing according to claim 8, characterized in that: The antioxidant is one or more of antioxidant 1076, antioxidant 3114 and antioxidant 1010.

10. The method for preparing a high-performance composite plastic for a new energy battery shell according to claim 9, characterized in that: The preparation method comprises the following steps: (1) mixing polypropylene, polyethylene, graphene, montmorillonite, and a coupling agent to obtain a graphene composite thermal conductor; (2) mixing the graphene composite thermal conductor with a toughening agent, a dispersant and an antioxidant to obtain a graphene composite thermal conductive plastic blend; (3) The graphene composite thermal conductive plastic blend is extruded and granulated to obtain the high-performance composite plastic.

Citation Information

Patent Citations

  • Compound plastic and lithium ion battery and battery pack manufactured by using same and assembling method thereof

    CN102558654A